Hydrothermal Synthesis and Crystal Structure of [Pyridine-2,6-dicarboxylato-\k: N,O,O'](pyrrole-\k:N)]copper(II) - Li, S.H.; Zhu, M. (Asian Journal of Chemistry, 2014)
One new copper complex of CuCl2·4H2O, pyrrole and pyridine-2,6-dicarboxylic acid has been successfully synthesized. The complex shows a one-dimensional framework. The 1D supramolecular structure is formed via hydrogen bonding connection.